Ecological or Controlled? Building Discursively Conscious Consumers - Borelli, Fernanda Chagas (2012)
In a context in which consumption has been identified as largely responsible for the destruction of resources and the imbalance of the Earth's climate, consumers are being asked to take action. Thus a group of consumers concerned about the effects of their purchases in the outside world has appeared a group we shall call conscious consumers. This work aims to help understand the dominant discourses on conscious consumption, investigating how consumers discursively construct the conscious consumer, the motivations, the practices, and the difficulties. The research was based on a projective exercise inspired by Belk, Deninney and Eckhardt‟s (2005) study. Thirtyseven students at a private university located in the suburb of the city of Rio de Janeiro took part on this exercise. Respondents outlined two discursive constructions for the conscious consumer, constructed from a strong duality with what they called the unconscious consumer. Motivations, behavior changes, and difficulties faced by these consumers were discussed and inspired management applications and paths for future research.